2007
DOI: 10.1111/j.1365-3156.2007.01959.x
|View full text |Cite
|
Sign up to set email alerts
|

Infant mortality among twins and triplets in rural Bangladesh in 1975–2002

Abstract: SummaryTo examine trends in incidence of multiple births (MB) and their survival in infancy, we used population-based, longitudinal data derived from the Health and Demographic Surveillance System in Matlab, Bangladesh, from 1975 to 2002. Logistic regression was applied to determine the impact of a number of variables on mortality among MB in the first year of life. MB averaged 2% of all live births, but contributed 10% to all infant deaths. Infant mortality among MB was more than five times higher than among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 13 publications
7
17
0
Order By: Relevance
“…Therefore, mortality of these highrisk groups contributes to the higher rate of childhood mortality especially during the early period of life. This fi nding is consistent with earlier studies conducted elsewhere 28,47,48,49,50 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Therefore, mortality of these highrisk groups contributes to the higher rate of childhood mortality especially during the early period of life. This fi nding is consistent with earlier studies conducted elsewhere 28,47,48,49,50 .…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with earlier studies 18,28,29,30 , the fi ndings of this study revealed that the higher the mother's education the lower the risk of neonatal mortality. A review of the literature shows that while the higher socioeconomic status of better educated women explains about half of the magnitude of the relationship between maternal education and child survival 31 , the domestic health practice of individual women is probably the new most salient mechanism in the maternal education child mortality relationship.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In Northern India, multiple births represented only 2.0% of all births and 1.9% of live births, but were associated with significantly increased risk of either stillbirth or neonatal death (Williams, Hossain, Sharma, Kumar, Pandey & Baqui 2008:324). Another study in Nigeria support claims that children born of multiple births are more likely to die during the first year of life than In Bangladesh, the infant mortality of twins and triplets was nearly seven times higher than that of singletons (356 vs 53 per 1,000 live births in 1995-2002), and it was eight times higher in the neonatal period (Alam, Ginneken & Bosch 2007:1509. In Brazil, multiple pregnancies were also associated with intrauterine growth restriction and preterm birth, which may consequently be associated with decreased neonatal survival rates (Lívia, Viola & Fernando 2011:228…”
Section: Type Of Birth (Singleton/multiple Pregnancy)mentioning
confidence: 92%
“…In Bangladesh, the neonatal mortality of twins and triplets was nearly eight times higher than that of singletons (356 vs 53 per 1,000 live births in [1995][1996][1997][1998][1999][2000][2001][2002], (Alam, Ginneken & Bosch 2007:1509. A study in Brazil also noted that multiple pregnancies are associated with IUGR and preterm birth, and may consequently be associated with decreased neonatal survival rates (Lívia et al 2011:228).…”
Section: Birth Typementioning
confidence: 99%